Platelet-derived mitochondria transfer facilitates wound-closure by modulating ROS levels in dermal fibroblasts. (31st December 2023) - Kim, Soomin; Kim, Yujin; Yu, Shin-Hye; Lee, Seo-Eun; Park, Jong Hyeok; Cho, Gayoung; Choi, Chul; Han, Kyuboem; Kim, Chun-Hyung; Kang, Young Cheol
Abstract: Platelets are known to improve the wound-repair capacity of mesenchymal stem cells (MSCs) by transferring mitochondria intercellularly. This study aimed to investigate whether direct transfer of mitochondria (pl-MT) isolated from platelets could enhance wound healing in vitro using a cell-based model. Wound repairs were assessed by 2D gap closure experiment in wound scratch assay using human dermal fibroblasts (hDFs). Results demonstrated that pl-MT were successfully internalized into hDFs. It increased cell proliferation and promoted the closure of wound gap. Importantly, pl-MT suppressed both intracellular and mitochondrial ROS production induced by hydrogen peroxide, cisplatin, and TGF-β in hDFs. Taken together, these results suggest that pl-MT transfer might be used as a potential therapeutic strategy for wound repair. Plain Language Summary: What is the context? During the wound healing process, abnormal regulation of ROS and inflammation delays the healing process, resulting in chronic non-healing wounds. Mitochondria are key organelles responsible for the ROS generation. Mitochondrial dysfunction has been implicated in delayed wound repair. Mitochondria transfer, which utilizes intact mitochondria isolated from healthy cells to recover from disease, has been applied in various clinical studies, but additional evidence is needed to apply it to wound healing. What is new? In this study, we chose platelets as a cell source for mitochondrial transfer. We isolated the functional mitochondria from platelets and applied them to wound healing. What is the impact? This study provides evidence that platelet-derived mitochondria (pl-MT) improve the wound healing progress by increasing the viability of dermal fibroblasts and suppressing intracellular and mitochondrial ROS production. Platelets have also been demonstrated to be a suitable cell source for mitochondrial transfer